2016
DOI: 10.3847/0004-637x/824/2/98
|View full text |Cite
|
Sign up to set email alerts
|

Line Broadening and the Solar Opacity Problem

Abstract: The calculation of line widths constitutes theoretical and computational challenges in the calculation of opacities of hot dense plasmas. Opacity models use line broadening approximations that are untested at stellar interior conditions. Moreover, calculations of atomic spectra of the sun, indicate a large discrepancy in the K-shell line widths between several atomic codes and the OP. In this work, the atomic code STAR is used to study the sensitivity of solar opacities to line-broadening. Variations in the so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…SOLAR RADIATIVE ZONE The complicated interactions between an ion and its environment give rise to important phenomena such as collisional line broadening (Dimitrijevic & Konjevic (1987); Krief et al (2016a)) and ionization potential depression (Ciricosta et al (2016)). In addition, the plasma environment affects the local atomic potential and the boundary conditions of atomic wavefunctions.…”
Section: The Effect Of Ion Correlation In Thementioning
confidence: 99%
“…SOLAR RADIATIVE ZONE The complicated interactions between an ion and its environment give rise to important phenomena such as collisional line broadening (Dimitrijevic & Konjevic (1987); Krief et al (2016a)) and ionization potential depression (Ciricosta et al (2016)). In addition, the plasma environment affects the local atomic potential and the boundary conditions of atomic wavefunctions.…”
Section: The Effect Of Ion Correlation In Thementioning
confidence: 99%
“…As mentioned in Section 4, a study of line profiles in opacity calculations has shown that OP K-line widths are largely discrepant with those in other plasma models in conditions akin to the solar CZB [27]. Such a finding in fact reflects essential differences in the treatment of ionic models in opacity calculations; i.e., between the OP multichannel representations (see Figure 1) and the simpler uncoupled, or in some cases statistical, versions adopted by other projects that become particularly conspicuous in spectator-electron processes.…”
Section: Line Resonance and Edge Profilesmentioning
confidence: 92%
“…In particular we discuss spectator-electron processes responsible for the broad and asymmetric resonances arising from core photoexcitation, K-shell resonance widths, and ionization edges since it has been recently shown that the solar opacity profile is sensitive to the Stark broadening of K lines [27].…”
Section: Introductionmentioning
confidence: 99%
“…The equation of state used by different groups to compute the tables may explain some of the differences 4 . However, the large differences observed in the Bailey et al (2015) experiment results may also be linked to other issues in current opacity computations (Nahar and Pradhan, 2016;Krief et al, 2016;Pain and Gilleron, 2019). Figure 8.…”
Section: Modified Solar Modelsmentioning
confidence: 97%